Casting CPE composite membrane material and preparation method thereof

By using a three-layer co-extrusion structure design and introducing functional components, the problems of insufficient flame retardancy, anti-aging and antistatic properties of cast CPE composite film materials have been solved, realizing a multifunctional and high-performance cast CPE composite film material.

CN120863174APending Publication Date: 2025-10-31QINGDAO WEIDONG PACKAGING CO LTD

Patent Information

Application Number
CN202511176114.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-21
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing cast CPE composite film materials lack flame retardant, anti-aging and antistatic properties, posing safety hazards and having a limited service life.

Method used

The product adopts a three-layer co-extrusion structure design, with the corona layer, intermediate core layer and heat-sealing layer each containing specific components. The corona layer is mainly composed of LLDPE, the intermediate core layer adds modified nano-silica to provide flame retardant and anti-aging functions, and the heat-sealing layer adds antistatic agents to achieve multifunctionality.

Benefits of technology

It achieves multifunctionality of cast CPE composite film material, possessing flame retardant, anti-aging and antistatic properties, while maintaining excellent heat-sealing performance and mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005559505300000101
    Figure BDA0005559505300000101
  • Figure BDA0005559505300000102
    Figure BDA0005559505300000102
  • Figure BDA0005559505300000111
    Figure BDA0005559505300000111
Patent Text Reader

Abstract

The invention relates to the technical field of plastic packaging films, in particular to a casting CPE composite film material and a preparation method thereof.The casting CPE composite film material is characterized in that a corona layer is prepared from, by weight, 72-75 parts of LLDPE, 18-22 parts of LDPE, 5-6 parts of EVA and 1.5-2 parts of an opening slipping agent; the middle core layer is prepared from the following components in parts by weight: 70 to 75 parts of LLDPE (Linear Low Density Polyethylene), 20 to 25 parts of HDPE (High Density Polyethylene), 5 to 8 parts of mPE, 3 to 5 parts of modified nano silicon dioxide and 1 to 3 parts of processing aid; the heat sealing layer is prepared from the following components in parts by weight: 25 to 30 parts of mLLDPE, 68 to 72 parts of LDPE, 0.3 to 0.5 part of antistatic agent and 1 to 2 parts of processing aid. The prepared composite film material has multiple functions of flame retardance, aging resistance, static electricity resistance and the like on the basis of keeping excellent heat sealing performance and mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of plastic packaging films, and more particularly to a cast CPE composite film material and its preparation method. Background Technology

[0002] Cast polyethylene (CPE) composite film is an important packaging material widely used in the food, pharmaceutical, and chemical industries. This type of film is prepared through a casting process and features good transparency, excellent heat-sealing performance, and high mechanical strength. Cast CPE composite films typically employ multi-layer co-extrusion technology, bonding together polyethylene layers with different functions. The corona layer provides good printability, the core layer provides mechanical strength and barrier properties, and the heat-sealing layer ensures the packaging's airtightness. As the packaging industry's requirements for material performance continue to increase, cast CPE composite films need to possess additional functions while maintaining basic packaging capabilities, such as antistatic, flame-retardant, and anti-aging properties.

[0003] Existing patent CN201910868705.8 discloses a CPE heat-sealing composite film, which comprises a three-layer structure of a corona layer, an intermediate layer, and a heat-sealing layer. The corona layer contains 64-68 parts LLDPE, 18-22 parts LDPE, 4-6 parts POE, 2-4 parts MPE, 0.8-1.2 parts opening slip agent, and 0.8-1.2 parts modified heat-sealing material; the intermediate layer contains 78-82 parts LLDPE, 8-12 parts LDPE, and 8-10 parts HDPE; the heat-sealing layer contains 8-12 parts mLLDPE, 5-7 parts modified heat-sealing material, 18-22 parts LDPE, 42-46 parts LLDPE, and 1.8-2.2 parts processing aids. However, the existing technology has the following drawbacks: First, the film material lacks effective flame retardant and anti-aging functions, posing safety hazards and limited service life in certain special application environments; second, the technical solution does not consider antistatic properties, and static electricity is easily generated in dry environments, affecting the safety and efficiency of packaging operations. Summary of the Invention

[0004] In view of this, the present invention proposes a cast CPE composite film material and its preparation method to solve the technical problems of existing cast CPE composite films lacking multifunctionality such as flame retardancy, anti-aging, and antistatic properties, and whose overall performance needs to be improved.

[0005] The technical solution of this invention is achieved as follows: This invention provides a cast CPE composite film material, comprising a corona layer, an intermediate core layer, and a heat-sealing layer connected in sequence.

[0006] The corona layer comprises the following components in parts by weight: 72-75 parts LLDPE, 18-22 parts LDPE, 5-6 parts EVA, and 1.5-2 parts opening slip agent;

[0007] The intermediate core layer comprises the following components in parts by weight: 70-75 parts LLDPE, 20-25 parts HDPE, 5-8 parts mPE, 3-5 parts modified nano-silica, and 1-3 parts processing aids.

[0008] The heat-sealing layer comprises the following components in parts by weight: 25-30 parts mLLDPE, 68-72 parts LDPE, 0.3-0.5 parts antistatic agent, and 1-2 parts processing aid.

[0009] The cast CPE composite film provided by this invention adopts a three-layer co-extrusion structure design. The corona layer is responsible for printability and surface functionality, with LLDPE as the main substrate, combined with LDPE to improve melt flow and surface smoothness, EVA as a compatibilizer to enhance interlayer adhesion, and an opening slip agent to provide excellent opening and slip properties. The middle core layer serves as the load-bearing skeleton and functional core of the composite film, with LLDPE as the matrix, HDPE added to provide rigidity and mechanical strength, mPE to improve processing flow, and modified nano-silica to impart flame retardant and anti-aging functions to the film. Processing aids optimize melt processing performance. The heat-sealing layer is responsible for packaging sealing and antistatic functions, with mLLDPE providing low-temperature heat-sealing performance, LDPE as the main substrate, antistatic agents to eliminate static electricity accumulation, and processing aids to assist molding processing. The three-layer structure synergistically realizes the multifunctionality and high performance of the cast CPE composite film.

[0010] Based on the above technical solutions, the preferred methods for preparing modified nano-silica include:

[0011] (1) Nano-silica is pretreated by immersing it in an acid solution to obtain activated silica;

[0012] (2) Under nitrogen protection, activated silica was dispersed in toluene, triethylamine was added, phosphorus oxychloride was added under ice bath conditions, and then the temperature was raised to 70-80℃ and reacted for 4.5-5.5h. After the reaction was completed, the temperature was cooled to room temperature, and 4-hydroxy-2,2,6,6-tetramethylpiperidine was added under nitrogen protection. Then the system was heated to 80-90℃ and kept at that temperature for 6-7h to obtain modified nano silica.

[0013] Specifically, in step (1), the silanol groups on the surface of nano-silica are fully exposed and activated by acid solution pretreatment, removing surface impurities and moisture, providing more reactive sites for subsequent organic modification, and improving modification efficiency; in step (2), in the presence of triethylamine, phosphorus oxychloride reacts with the silanol groups on the activated silica surface to generate Si-OP(O)Cl2 bond structure. Triethylamine acts as an HCl acid-binding agent to promote the reaction. Then, the added 4-hydroxy-2,2,6,6-tetramethylpiperidine reacts with the phosphoryl chloride group to form a stable phosphate ester bond, grafting the hindered amine group onto the silica surface. Through the above chemical modification, not only is the dispersion and compatibility of nano-silica in the polymer matrix significantly improved, but more importantly, a phosphorus-nitrogen synergistic flame retardant mechanism and hindered amine light stabilizer function are introduced, giving the composite film good flame retardant and anti-aging properties.

[0014] Based on the above technical solutions, preferably, in step (1), the acid solution is a dilute hydrochloric acid solution with a mass fraction of 15-20%, the pretreatment temperature is 55-65℃, and the time is 2-4h.

[0015] Based on the above technical solutions, preferably, in step (2), the mass ratio of activated silica, triethylamine, phosphorus oxychloride and 4-hydroxy-2,2,6,6-tetramethylpiperidine is 10:(2.5-3.5):(1.2-1.8):(3.0-4.0).

[0016] Based on the above technical solutions, the preferred antistatic agents include bis(β-hydroxyethyl)cocoamine and 1-hexyl-3-methylimidazolium chloride.

[0017] Based on the above technical solutions, the preferred mass ratio of bis(β-hydroxyethyl)cocoamine and 1-hexyl-3-methylimidazolium chloride is (3-5):1.

[0018] The antistatic agent is a compound system of bis(β-hydroxyethyl)cocoamine and 1-hexyl-3-methylimidazolium chloride. The long-chain coconut oil groups in the bis(β-hydroxyethyl)cocoamine molecule provide good hydrophobicity, ensuring excellent compatibility and dispersibility of the antistatic agent in the polyethylene matrix. The β-hydroxyethyl group is hydrophilic and can adsorb trace amounts of moisture in the environment to form a conductive path. 1-Hexyl-3-methylimidazolium chloride, as an ionic liquid, has conductivity and excellent thermal stability, and is the core function to provide rapid and efficient antistatic performance. When the two are compounded, the long-chain structure of the cocoamine molecule can effectively "coat" and "anchor" the ionic liquid molecule, which not only gives full play to the efficient antistatic performance of the ionic liquid, but also solves the problem of poor compatibility and easy leakage of ionic liquid in non-polar polymers through cocoamine. This achieves continuous and stable control of the surface resistivity of the composite membrane, giving the membrane long-term and stable antistatic performance and effectively preventing the accumulation of static electricity during production and use.

[0019] Based on the above technical solutions, preferably, the processing aid is a plasticizer and / or a compatibilizer.

[0020] Based on the above technical solutions, preferably, the plasticizer is a polyol or dibutyl phthalate, and the compatibilizer is one or more of acrylic acid, methacrylic acid, and maleic anhydride.

[0021] Based on the above technical solutions, preferably, the LLDPE in the corona layer has a melt index of 2.0-4.0 g / 10 min and a density of 0.918-0.920 g / cm³. 3 The melt index of LDPE is 4.0-8.0 g / 10 min, and the density is 0.920-0.925 g / cm³. 3 The melt flow index of EVA is 2.0-5.0 g / 10 min, and its density is 0.930-0.940 g / cm³. 3 ;

[0022] The LLDPE in the intermediate core layer has a melt index of 1.5-3.0 g / 10 min and a density of 0.918-0.920 g / cm³. 3 HDPE has a melt index of 4.0-7.5 g / 10 min and a density of 0.950-0.960 g / cm³. 3 The melt flow index of mPE is 1.5-3.5 g / 10 min, and the density is 0.918-0.928 g / cm³. 3 ;

[0023] The melt index of mLLDPE in the heat-sealing layer is 2.5-4.5 g / 10 min, and the density is 0.915-0.918 g / cm³. 3The melt index of LDPE is 5.0-8.0 g / 10 min, and the density is 0.922-0.925 g / cm³. 3 .

[0024] This invention provides a method for preparing a cast CPE composite film, the method comprising the following steps: weighing raw materials according to the raw material ratios of the heat-sealing layer, the intermediate core layer, and the corona layer; mixing the raw materials of each layer uniformly to obtain a heat-sealing layer blend, an intermediate core layer blend, and a corona layer blend; adding the heat-sealing layer blend, the intermediate core layer blend, and the corona layer blend to a three-layer co-extrusion device, and performing melt extrusion, casting, and corona treatment to obtain a cast CPE composite film.

[0025] The cast CPE composite film and its preparation method of the present invention have the following advantages over the prior art:

[0026] (1) By designing a three-layer co-extrusion structure and introducing functional components in each layer, the multifunctional integration of cast CPE composite film material is realized. The EVA compatibilizer design of the corona layer ensures the interlayer bonding strength. The modified nano silica in the middle core layer gives the film material flame retardant and anti-aging properties. The antistatic agent compound system of the heat-sealing layer provides long-lasting antistatic function. The synergistic effect of the three layers enables the composite film material to have multiple functions such as flame retardant, anti-aging and antistatic while maintaining excellent heat-sealing performance and mechanical strength.

[0027] (2) By constructing phosphorus-nitrogen synergistic functional groups on the surface of nano silica, its dispersibility and interfacial compatibility in polyethylene matrix are significantly improved. The modified nano silica not only plays the reinforcing effect of nano filler, but more importantly, it introduces the dual functions of hindered amine light stabilizer and phosphorus flame retardant, so that the composite film has excellent anti-aging performance under ultraviolet light irradiation and can form a dense carbon layer to prevent flame propagation during combustion, thus realizing the multifunctionality of a single component.

[0028] (3) By combining bis(β-hydroxyethyl)cocoamine with 1-hexyl-3-methylimidazolium chloride, the synergistic antistatic mechanism of carrier-functional core is fully utilized. The long-chain aliphatic structure of cocoamine solves the problem of poor compatibility and easy leakage of ionic liquid in polyethylene, while the intrinsic conductivity of ionic liquid ensures rapid and efficient electrostatic discharge capability. The compound system keeps the surface resistivity of the composite film material stably controlled within the antistatic requirement range, and the antistatic performance is long-lasting and stable. Detailed Implementation

[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0030] Unless otherwise specified, all raw materials used in the examples are commercially available. Specifically, the m-LLDPE in the heat-sealing layer has a melt flow index of 3.8 g / 10 min and a density of 0.903 g / cm³. 3 The model number is SP0540; the density of LDPE is 0.92 g / cm³. 3 The melt flow index was 4 g / 10 min, selected from JPC LB625 (Japan); the melt flow index of LLDPE in the intermediate core layer was 2.3 g / 10 min, and the density was 0.918 g / cm³. 3 The model number is 2067G; the melt flow index of mPE is 3.5 g / 10 min, and the density is 0.927 g / cm³. 3 The model is Lumicene mPE M 2735; the HDPE melt index is 7.5 g / 10 min, and the density is 0.956 g / cm³. 3 The product model is FMA026TG; the melt index of LLDPE in the corona layer is 3.8 g / 10 min, and the density is 0.923 g / cm³. 3 The model number is SP2540R; the melt index of LDPE is 4 g / 10 min, and the density is 0.923 g / cm³. 3 The model number is FD0474; the EVA melt index is 2 g / 10 min, and the density is 0.934 g / cm³. 3 The model number is E180F. The slip agent is 10090-K, and the opening agent is AB-MB-09.

[0031] Example 1

[0032] This embodiment provides a cast CPE composite film material, wherein the corona layer comprises 74 parts LLDPE, 20 parts LDPE, 5.5 parts EVA, and 1.8 parts of opening slip agent (mixed by mixing opening agent and slip agent in a mass ratio of 1:1); the intermediate core layer comprises 73 parts LLDPE, 23 parts HDPE, 6.5 parts mPE, 4 parts modified nano silica, and 2 parts processing aid (mixed by mixing dibutyl phthalate and methacrylic acid in a mass ratio of 1:1); the heat-sealing layer comprises 28 parts mLLDPE, 70 parts LDPE, 0.4 parts antistatic agent, and 1.5 parts dibutyl phthalate, wherein the antistatic agent is bis(β-hydroxyethyl)cocoamine and 1-hexyl-3-methylimidazolium chloride in a mass ratio of 4:1.

[0033] Methods for preparing modified nano-silica include:

[0034] (1) 100g of nano silica was immersed in a dilute hydrochloric acid solution with a mass fraction of 18%, activated at 60°C for 3h, filtered, washed with deionized water until neutral, and vacuum dried at 80°C for 6h to obtain activated silica.

[0035] (2) Under nitrogen protection, 100g of activated silica was dispersed in toluene and ultrasonically dispersed evenly. 30g of triethylamine was added, and 15g of phosphorus oxychloride was slowly added dropwise under ice bath conditions. After the addition was completed, the temperature was raised to 70-80℃ and reacted for 5.0h. After the reaction was completed, the temperature was cooled to room temperature. Under nitrogen protection, 35g of 4-hydroxy-2,2,6,6-tetramethylpiperidine was added. The temperature was then raised to 85℃ and kept at that temperature for 6.5h. After the reaction was completed, the temperature was naturally cooled to room temperature. The product was collected by centrifugation and washed three times each with ethanol and acetone. The product was then dried under vacuum to obtain modified nano silica.

[0036] The preparation method of cast CPE composite film includes: weighing raw materials according to the raw material ratio of heat-sealing layer, intermediate core layer and corona layer, mixing each layer of raw materials evenly to obtain heat-sealing layer blend, intermediate core layer blend and corona layer blend; adding the heat-sealing layer blend, intermediate core layer blend and corona layer blend to a three-layer co-extrusion device, with the extrusion temperature of each layer set as follows: heat-sealing layer 160-245℃ (5 temperature gradient zones), intermediate core layer 165-235℃, corona layer 170-230℃, and the die temperature uniformly set to 225℃. After melt extrusion, the film is cast onto a cooling roller through a T-die and formed on a 25℃ cooling roller to obtain the film material. Subsequently, the corona layer side of the film material is subjected to corona treatment with a power of 2.8kW to make its surface tension reach 40 dynes, and finally wound up to obtain the cast CPE composite film material.

[0037] Example 2

[0038] This embodiment provides a cast CPE composite film material, wherein the corona layer comprises 72 parts LLDPE, 18 parts LDPE, 5 parts EVA, and 1.5 parts of opening slip agent (mixed by mixing opening agent and slip agent in a mass ratio of 1:1); the intermediate core layer comprises 70 parts LLDPE, 20 parts HDPE, 5 parts mPE, 3 parts modified nano silica, and 1 part processing aid (mixed by mixing dibutyl phthalate and methacrylic acid in a mass ratio of 1:1); the heat-sealing layer comprises 25-30 parts mLLDPE, 68-72 parts LDPE, 0.3 parts antistatic agent, and 1 part dibutyl phthalate, wherein the antistatic agent is bis(β-hydroxyethyl)cocoamine and 1-hexyl-3-methylimidazolium chloride in a mass ratio of 3:1.

[0039] Methods for preparing modified nano-silica include:

[0040] (1) Immerse 100g of nano silica in a 15% dilute hydrochloric acid solution, activate at 55°C for 4h, filter, wash with deionized water until neutral, and vacuum dry at 80°C for 6h to obtain activated silica.

[0041] (2) Under nitrogen protection, 100g of activated silica was dispersed in toluene and ultrasonically dispersed evenly. 25g of triethylamine was added, and 12g of phosphorus oxychloride was slowly added dropwise under ice bath conditions. After the addition was completed, the temperature was raised to 70℃ and reacted for 5.5h. After the reaction was completed, the temperature was cooled to room temperature. Under nitrogen protection, 30g of 4-hydroxy-2,2,6,6-tetramethylpiperidine was added. The temperature was then raised to 80℃ and kept at that temperature for 7h. After the reaction was completed, the temperature was naturally cooled to room temperature. The product was collected by centrifugation and washed three times each with ethanol and acetone. The product was then dried under vacuum to obtain modified nano silica.

[0042] The preparation method of cast CPE composite film includes: weighing raw materials according to the raw material ratio of heat-sealing layer, intermediate core layer and corona layer, mixing each layer of raw materials evenly to obtain heat-sealing layer blend, intermediate core layer blend and corona layer blend; adding the heat-sealing layer blend, intermediate core layer blend and corona layer blend to a three-layer co-extrusion device, with the extrusion temperature of each layer set as follows: heat-sealing layer 160-245℃ (5 temperature gradient zones), intermediate core layer 165-235℃, corona layer 170-230℃, and the die temperature uniformly set to 225℃. After melt extrusion, the film is cast onto a cooling roller through a T-die and formed on a 25℃ cooling roller to obtain the film material. Subsequently, the corona layer side of the film material is subjected to corona treatment with a power of 2.8kW to make its surface tension reach 40 dynes, and finally wound up to obtain the cast CPE composite film material.

[0043] Example 3

[0044] This embodiment provides a cast CPE composite film material, wherein the corona layer comprises 75 parts LLDPE, 22 parts LDPE, 6 parts EVA, and 2 parts opening slip agent (mixed by mixing opening agent and slip agent in a mass ratio of 1:1); the intermediate core layer comprises 75 parts LLDPE, 25 parts HDPE, 8 parts mPE, 5 parts modified nano silica, and 3 parts processing aid (mixed by mixing dibutyl phthalate and methacrylic acid in a mass ratio of 1:1); the heat-sealing layer comprises 30 parts mLLDPE, 72 parts LDPE, 0.5 parts antistatic agent, and 2 parts dibutyl phthalate, wherein the antistatic agent is bis(β-hydroxyethyl)cocoamine and 1-hexyl-3-methylimidazolium chloride in a mass ratio of 5:1.

[0045] Methods for preparing modified nano-silica include:

[0046] (1) Immerse 100g of nano silica in a 20% dilute hydrochloric acid solution, activate at 65°C for 2h, filter, wash with deionized water until neutral, and vacuum dry at 80°C for 6h to obtain activated silica.

[0047] (2) Under nitrogen protection, 100g of activated silica was dispersed in toluene and ultrasonically dispersed evenly. 35g of triethylamine was added, and 18g of phosphorus oxychloride was slowly added dropwise under ice bath conditions. After the addition was completed, the temperature was raised to 80℃ and reacted for 4.5h. After the reaction was completed, the temperature was cooled to room temperature. Under nitrogen protection, 40g of 4-hydroxy-2,2,6,6-tetramethylpiperidine was added. The temperature was then raised to 90℃ and kept at that temperature for 6h. After the reaction was completed, the temperature was naturally cooled to room temperature. The product was collected by centrifugation and washed three times each with ethanol and acetone. The product was then dried under vacuum to obtain modified nano silica.

[0048] The preparation method of cast CPE composite film includes: weighing raw materials according to the raw material ratio of heat-sealing layer, intermediate core layer and corona layer, mixing each layer of raw materials evenly to obtain heat-sealing layer blend, intermediate core layer blend and corona layer blend; adding the heat-sealing layer blend, intermediate core layer blend and corona layer blend to a three-layer co-extrusion device, with the extrusion temperature of each layer set as follows: heat-sealing layer 160-245℃ (5 temperature gradient zones), intermediate core layer 165-235℃, corona layer 170-230℃, and the die temperature uniformly set to 225℃. After melt extrusion, the film is cast onto a cooling roller through a T-die and formed on a 25℃ cooling roller to obtain the film material. Subsequently, the corona layer side of the film material is subjected to corona treatment with a power of 2.8kW to make its surface tension reach 40 dynes, and finally wound up to obtain the cast CPE composite film material.

[0049] Comparative Example 1

[0050] This comparative example provides a cast CPE composite film material, wherein the corona layer comprises 74 parts LLDPE, 20 parts LDPE, 5.5 parts EVA, and 1.8 parts of an opening slip agent (mixed by mass ratio of opening agent and slip agent in a 1:1 ratio); the intermediate core layer comprises 73 parts LLDPE, 23 parts HDPE, 6.5 parts mPE, 4 parts modified nano-silica, and 2 parts processing aid (mixed by mass ratio of dibutyl phthalate and methacrylic acid in a 1:1 ratio); and the heat-sealing layer comprises 28 parts mLLDPE, 70 parts LDPE, 0.4 parts antistatic agent, and 1.5 parts dibutyl phthalate. The preparation method is the same as in Example 1, except that the antistatic agent is bis(β-hydroxyethyl)cocoamine.

[0051] Comparative Example 2

[0052] This comparative example provides a cast CPE composite film material, wherein the corona layer comprises 74 parts LLDPE, 20 parts LDPE, 5.5 parts EVA, and 1.8 parts of an opening slip agent (mixed by mass ratio of opening agent and slip agent in a 1:1 ratio); the intermediate core layer comprises 73 parts LLDPE, 23 parts HDPE, 6.5 parts mPE, 4 parts modified nano-silica, and 2 parts processing aid (mixed by mass ratio of dibutyl phthalate and methacrylic acid in a 1:1 ratio); and the heat-sealing layer comprises 28 parts mLLDPE, 70 parts LDPE, 0.4 parts antistatic agent, and 1.5 parts dibutyl phthalate. The preparation method is the same as in Example 1, except that the antistatic agent is 1-hexyl-3-methylimidazolium chloride.

[0053] Comparative Example 3

[0054] This comparative example provides a cast CPE composite film material, wherein the corona layer comprises 74 parts LLDPE, 20 parts LDPE, 5.5 parts EVA, and 1.8 parts of an opening slip agent (mixed by mass ratio of opening agent and slip agent in a 1:1 ratio); the intermediate core layer comprises 73 parts LLDPE, 23 parts HDPE, 6.5 parts mPE, 4 parts modified nano-silica, and 2 parts processing aid (mixed by mass ratio of dibutyl phthalate and methacrylic acid in a 1:1 ratio); and the heat-sealing layer comprises 28 parts mLLDPE, 70 parts LDPE, 0.4 parts antistatic agent, and 1.5 parts dibutyl phthalate. The preparation method is the same as in Example 1, except that:

[0055] Methods for preparing modified nano-silica include:

[0056] (1) 100g of nano silica was immersed in a dilute hydrochloric acid solution with a mass fraction of 18%, activated at 60°C for 3h, filtered, washed with deionized water until neutral, and vacuum dried at 80°C for 6h to obtain activated silica.

[0057] (2) Under nitrogen protection, 100g of activated silica was dispersed in toluene and ultrasonically dispersed evenly. 30g of triethylamine was added, and 15g of phosphorus oxychloride was slowly added dropwise under ice bath conditions. After the addition was completed, the temperature was raised to 70-80℃ and reacted for 5.0h. After the reaction was completed, the temperature was cooled to room temperature, and the product was collected by centrifugation. The product was washed three times each with ethanol and acetone, and then dried under vacuum to obtain modified nano silica.

[0058] Comparative Example 4

[0059] This comparative example provides a cast CPE composite film material, wherein the corona layer comprises 74 parts LLDPE, 20 parts LDPE, 5.5 parts EVA, and 1.8 parts of an opening slip agent (mixed by mass ratio of opening agent and slip agent in a 1:1 ratio); the intermediate core layer comprises 73 parts LLDPE, 23 parts HDPE, 6.5 parts mPE, 4 parts modified nano-silica, and 2 parts processing aid (mixed by mass ratio of dibutyl phthalate and methacrylic acid in a 1:1 ratio); and the heat-sealing layer comprises 28 parts mLLDPE, 70 parts LDPE, 0.4 parts antistatic agent, and 1.5 parts dibutyl phthalate. The preparation method is the same as in Example 1, except that:

[0060] Preparation method of modified nano-silica:

[0061] (1) 100g of nano silica was immersed in a dilute hydrochloric acid solution with a mass fraction of 18%, activated at 60°C for 3h, filtered, washed with deionized water until neutral, and vacuum dried at 80°C for 6h to obtain activated silica.

[0062] (2) 100g of activated silica, 15g of phosphorus oxychloride, and 35g of 4-hydroxy-2,2,6,6-tetramethylpiperidine were physically mixed in a high-speed mixer for 10 minutes to obtain modified nano silica.

[0063] Performance testing

[0064] The performance of the cast CPE composite films prepared in the examples and comparative examples was tested. The test indicators included: transparency (tested according to GB / T2410-1980); tensile strength and elongation at break (tested according to GB / T13022-1991); heat-sealing performance (tested according to QB / T2358-1998); antistatic properties: the resistivity of the electrostatic layer was measured using a ZC36 high-insulation resistance meter; each example or comparative example film was measured three times, and the average value was taken. The testing instrument was an ST2263 (Suzhou Jingge Electronics Co., Ltd.) dual-electrical-measuring digital four-probe tester; flame retardancy (tested according to GB / T2406.2-2009); and anti-aging properties: tested using a wavelength of 340nm and a pre-irradiation intensity of 0.68W / m. 2 The experiment involved 3 hours of light exposure followed by 10 minutes of wind exposure, with the cycle repeated continuously for a total of 168 hours. After aging, the tensile strength retention rate was tested. The test results are shown in Tables 1 and 2.

[0065] Table 1 Performance Test 1

[0066]

[0067] Table 2 Performance Test 2

[0068]

[0069]

[0070] In summary, the cast CPE composite film prepared by the technical solution of this invention has high transparency, high tensile strength, high elongation at break, and strong mechanical properties. At the same time, due to the introduction of antistatic agents and modified nano-silica, it has excellent antistatic properties, flame retardancy, and anti-aging properties, thus improving the overall performance of the cast CPE composite film.

[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A cast CPE composite film material, characterized in that, It includes a corona layer, an intermediate core layer, and a heat-sealing layer connected in sequence. The corona layer comprises the following components in parts by weight: 72-75 parts LLDPE, 18-22 parts LDPE, 5-6 parts EVA, and 1.5-2 parts opening slip agent; The intermediate core layer comprises the following components in parts by weight: 70-75 parts LLDPE, 20-25 parts HDPE, 5-8 parts mPE, 3-5 parts modified nano-silica, and 1-3 parts processing aids. The heat-sealing layer comprises the following components in parts by weight: 25-30 parts mLLDPE, 68-72 parts LDPE, 0.3-0.5 parts antistatic agent, and 1-2 parts processing aid.

2. The cast CPE composite film material as described in claim 1, characterized in that: Methods for preparing modified nano-silica include: (1) Nano-silica is pretreated by immersing it in an acid solution to obtain activated silica; (2) Under nitrogen protection, activated silica was dispersed in toluene, triethylamine was added, phosphorus oxychloride was added under ice bath conditions, and then the temperature was raised to 70-80℃ and reacted for 4.5-5.5h. After the reaction was completed, the temperature was cooled to room temperature, and 4-hydroxy-2,2,6,6-tetramethylpiperidine was added under nitrogen protection. Then the system was heated to 80-90℃ and kept at that temperature for 6-7h to obtain modified nano silica.

3. The cast CPE composite film material as described in claim 2, characterized in that: In step (1), the acid solution is a dilute hydrochloric acid solution with a mass fraction of 15-20%, and the pretreatment temperature is 55-65℃ for 2-4 hours.

4. The cast CPE composite film material as described in claim 2, characterized in that: In step (2), the mass ratio of activated silica, triethylamine, phosphorus oxychloride and 4-hydroxy-2,2,6,6-tetramethylpiperidine is 10:(2.5-3.5):(1.2-1.8):(3.0-4.0).

5. The cast CPE composite film material as described in claim 1, characterized in that: Antistatic agents include bis(β-hydroxyethyl)cocoamine and 1-hexyl-3-methylimidazolium chloride.

6. The cast CPE composite film material as described in claim 5, characterized in that: The mass ratio of bis(β-hydroxyethyl)cocoamine to 1-hexyl-3-methylimidazolium chloride is (3-5):

1.

7. The cast CPE composite film material as described in claim 1, characterized in that: The processing aid is a plasticizer and / or a compatibilizer.

8. The cast CPE composite film material as described in claim 7, characterized in that: The plasticizer is a polyol or dibutyl phthalate, and the compatibilizer is one or more of acrylic acid, methacrylic acid, and maleic anhydride.

9. The cast CPE composite film material as described in claim 1, characterized in that: The corona layer contains LLDPE with a melt index of 2.0-4.0 g / 10 min and a density of 0.918-0.920 g / cm3; LDPE with a melt index of 4.0-8.0 g / 10 min and a density of 0.922-0.925 g / cm3; and EVA with a melt index of 2.0-5.0 g / 10 min and a density of 0.930-0.940 g / cm3. The LLDPE in the intermediate core layer has a melt index of 1.5-3.0 g / 10 min and a density of 0.918-0.920 g / cm³. 3 HDPE has a melt index of 4.0-7.0 g / 10 min and a density of 0.950-0.960 g / cm³. 3 The melt flow index of mPE is 1.5-3.5 g / 10 min, and the density is 0.918-0.920 g / cm3. The melt index of mLLDPE in the heat-sealing layer is 2.5-4.5 g / 10 min, and the density is 0.915-0.918 g / cm3; the melt index of LDPE is 5.0-8.0 g / 10 min, and the density is 0.922-0.925 g / cm3.

10. A method for preparing a cast CPE composite film as described in any one of claims 1-9, characterized in that: The preparation method includes the following steps: weighing raw materials according to the raw material ratio of heat-sealing layer, intermediate core layer and corona layer, mixing each layer of raw materials evenly to obtain heat-sealing layer blend, intermediate core layer blend and corona layer blend; adding heat-sealing layer blend, intermediate core layer blend and corona layer blend to a three-layer co-extrusion device, and performing melt extrusion, casting molding and corona treatment to obtain cast CPE composite film material.

Citation Information

Patent Citations

  • A CPE heat-sealing composite film and its preparation method

    CN110466225B

Cited By

  • Multilayer co-extrusion flame-retardant composite film and preparation method thereof

    CN122323634A

  • A multilayer co-extruded flame retardant composite film and a method for preparing the same

    CN122323634B